Analysis of Variance in Dry Concrete Production Using Simulation Models - Torres, Hernan (2010)
This project research seeks to analyse the impact of variance in the dry concrete manufacturing processing times with a simulation output performance measure, by studying the simulation model results and answering with quantitative units, how much the overall system performance gets affected if the variance is increased by one unit. Three main challenges provide difficulty to this study: to develop a clear understanding of the system to simulate, to represent it in a computational model and to draw valid conclusions on the measured impact based on the model results. Three groups of experiments establish the conditions of how the variability is inserted to the system stages by the creation of different simulation models. The first group of experiments considers variance modifications in all activities, the second group has variability changes in critical activities and the last group simulates machines breakdown and repairing time’s variability. An interesting relationship between the variance and some preselected performance measures is noticed. Graphs are plotted and most of the provided analysis is supported by tendency lines and statistical procedures. Finally, Conclusions are presented and a set of project proposals are identified for achieving a full understanding on the topic.